228k views
5 votes
Evaluate the function.
f(x) = x² + 2x + 6
Find f(-7)

2 Answers

4 votes

Answer: f(-7)=41

Explanation:

f(x) = x² + 2x + 6

f(-7)=(-7)² + 2(-7) + 6

f(-7)=49-14 + 6

f(-7)=35 + 6

f(-7)=41

User Adarsh Sojitra
by
5.3k points
3 votes

Answer:

f(-7) = 41

Explanation:

f(x) = x² + 2x + 6

In order to find f(-7) ,we just need to substitute x in the expression of the function f by -7.

Then

f(-7) = (-7)² + 2(-7) + 6

= 49 - 14 + 6

= 35 + 6

= 41

Evaluate the function. f(x) = x² + 2x + 6 Find f(-7)-example-1
User Wbdlc
by
5.6k points